TEKNOLOGI PERTANIAN TERINTEGRASI BERBASIS FILOSOFI TRI HITA KARANA DALAM USAHATANI MENUJU PERTANIAN ORGANIK - Ni Putu Sukanteri; Pande Komang Suparyana; I Made Suryana; I Made Dedy Setiawan (Faculty of Animal and Agricultural Science, Diponegoro University, 2019)
Technology Integration of cattle plants in farming is a breakthrough in accelerating the adoption of agricultural technology transfer to rural communities with the potential of each region that optimizes the use of local resources. Rainfed rice fields are a big obstacle in farming production so planning needs to be done in planting agricultural commodities. The aim of the study was to determine the profits and productivity of farming while applying agricultural integration technology to the Tani Suka Mandiri group, knowing the application of the Tri Hita Karana philosophy in the management of farming in the Suka Mandiri Tani Group, Megati Village, Selemadeg Timur District, Tabanan Regency, Bali Province.The results of research on farming profits obtained from rice farming during the implementation of agricultural integration technology innovations in Suka Mandiri farmer groups amounted to Rp. 17,925,570.00 with an R / C ratio of 2.22. The application of the Tri Hita Karana Philosophy was carried out in the farmer group of Mandiri Livestock namely to create harmony, between humans and the natural environment, and the implementation of rituals in farming, to create harmony between farmers during the management of farming and human-natural relations that can be seen by using organic inputs in agricultural areas in an effort to improve soil nutrients and obtain organic agricultural products sustainable. The productivity of rice farming after being obtained during the application of technological integration of plant innovation with cattle was obtained at 7.6 tons / ha, with efficiency above 80%.